2017
DOI: 10.1371/journal.pone.0179078
|View full text |Cite
|
Sign up to set email alerts
|

Generation of an immortalized mouse embryonic palatal mesenchyme cell line

Abstract: Palatogenesis is a complex morphogenetic process, disruptions in which result in highly prevalent birth defects in humans. In recent decades, the use of model systems such as genetically-modified mice, mouse palatal organ cultures and primary mouse embryonic palatal mesenchyme (MEPM) cultures has provided significant insight into the molecular and cellular defects underlying cleft palate. However, drawbacks in each of these systems have prevented high-throughput, large-scale studies of palatogenesis in vitro. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…To evaluate intracellular pathway activation downstream of wild-type FGFR2 and the FGFR2 F , FGFR2 CPG and FGFR2 FCPG signaling mutant receptors, we generated immortalized E10.5 FNP cell lines from the respective mouse strains also carrying a mutation in Ink4A/Arf to facilitate rapid immortalization of these cells. Similar to a previous study with palatal mesenchymal cells (Fantauzzo and Soriano 2017), we found that expression of facial mesenchyme markers was similar between primary and immortalized FNP cells (iFNPs; Supplementary Figure S4B). We isolated iFNPs for respective genotypes (wt-iFNP, F-iFNP, CPG-iFNP and FCPG-iFNP).…”
Section: Signaling Mutations Disrupt Multiple Intracellular Pathwayssupporting
confidence: 89%
“…To evaluate intracellular pathway activation downstream of wild-type FGFR2 and the FGFR2 F , FGFR2 CPG and FGFR2 FCPG signaling mutant receptors, we generated immortalized E10.5 FNP cell lines from the respective mouse strains also carrying a mutation in Ink4A/Arf to facilitate rapid immortalization of these cells. Similar to a previous study with palatal mesenchymal cells (Fantauzzo and Soriano 2017), we found that expression of facial mesenchyme markers was similar between primary and immortalized FNP cells (iFNPs; Supplementary Figure S4B). We isolated iFNPs for respective genotypes (wt-iFNP, F-iFNP, CPG-iFNP and FCPG-iFNP).…”
Section: Signaling Mutations Disrupt Multiple Intracellular Pathwayssupporting
confidence: 89%
“…To do this, primary MEPM cells were dissected from E13.5 control ( Pdgfra +/fl ;Wnt1-Cre +/Tg or Pdgfrb +/fl ;Wnt1-Cre +/Tg ) and conditional knock-out ( Pdgfra fl/fl ;Wnt1-Cre +/Tg or Pdgfrb fl/fl ;Wnt1-Cre +/Tg ) littermate embryos for use in cell growth assays (Figure 8A). Primary MEPM cells are a faithful surrogate for embryonic facial mesenchyme, as wild-type cells uniformly express both PDGFRα and PDGFRβ, as well as numerous additional markers of palatal mesenchyme cells in vivo , and are responsive to stimulation with PDGF-AA, PDGF-BB and PDGF-DD ligand (He and Soriano, 2013; Fantauzzo and Soriano, 2014, 2016, 2017; Vasudevan and Soriano, 2014; Vasudevan et al, 2015). Even after a single day in growth medium containing 10% FBS, control Pdgfrb +/fl ;Wnt1-Cre +/Tg cells (0.1077 ± 0.01233 arbitrary units (AU)) (Figure 8C) had grown about half as much as control Pdgfra +/fl ;Wnt1-Cre +/Tg cells (0.2217 ± 0.07322 AU) (Figure 8B).…”
Section: Resultsmentioning
confidence: 99%
“…This remodeling is likely initiated by the medial edge epithelium of the palatal shelf, but driven by the palate mesenchyme. While primary MEPM cells have been used for testing the effect of various inhibitory compounds, growth factors, and gene-expression changes (Fantauzzo and Soriano 2014;Gao et al 2019;Iyyanar and Nazarali 2017;Jiang et al 2017;Liu et al 2014;Vasudevan and Soriano 2014), only a few studies have investigated the migration of MEPM cells (Fantauzzo and Soriano 2017;Gao et al 2019;He and Soriano 2013), and none, to our knowledge, have examined if they can migrate collectively. We identify the presence of stream formation in MEPM cells, a behavior generally considered to be a feature of collective movement (Czirok et al 2013;Scarpa and Mayor 2016;Szabo et al 2010).…”
Section: Discussionmentioning
confidence: 99%